The Impact of Organizational Support on the Psychological Capital of the Employees of the Sonatrach Company of Biskra - Boussekar, Rabia; Zaoui, Souria; Bahouri, Nabil (Finance and Business Economies Review, 2022)
The study aims to try to determine the impact of organizational support on the psychological capital of workers in the Sonatrach Company in Biskra.We focused on the analysis and were lied on the descriptive analytical approach which corresponds to the nature of the study, because it allows studying the subject in its theoretical and practical aspect in a very precise way. A questionnaire was distributed to a group of employees in the management of Sonatrach company in the department of Biskra (54 employees), and we achieved a set of field results, the most important of which is that organizational support explains 29.9% of changes in psychological capital